1991
DOI: 10.1111/j.1745-4557.1991.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN QUALITY CHARACTERISTICS DURING PEACH (CV. ‘MAJESTIC’) MATURATION1

Abstract: Changes in the physical, chemical and sensory characteristics of peaches (cv. 'Majestic') were determined. Size, weight, ground color "a" values and SSITA ratio increased sign$cantly with increased degree of maturity; whereas, j r mness, DLE, hue angle, titratable acidity, quinic acid, and citric acid decreased signifcantly. Malic acid increased signijicantly with maturity up to grade 5 then signifcantly decreased. In general sucrose content and total sugars increased through grade 6 and then decreased for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
6
19
1
3
Order By: Relevance
“…It has been suggested that the ratio SS/TA indicates ripeness of fresh fruit and that fruit with a ratio greater than 15:l will ripen to high-quality fruit (Despande and Salunkhe, 1964). Our data show this ratio was reached at about maturity 4, in agreement with data we reported for other cultivars (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991. Results are similar to the characteristics of other cultivars grown at the University of Georgia Horticulture farm in previous years (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that the ratio SS/TA indicates ripeness of fresh fruit and that fruit with a ratio greater than 15:l will ripen to high-quality fruit (Despande and Salunkhe, 1964). Our data show this ratio was reached at about maturity 4, in agreement with data we reported for other cultivars (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991. Results are similar to the characteristics of other cultivars grown at the University of Georgia Horticulture farm in previous years (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991.…”
Section: Discussionsupporting
confidence: 95%
“…Our data show this ratio was reached at about maturity 4, in agreement with data we reported for other cultivars (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991. Results are similar to the characteristics of other cultivars grown at the University of Georgia Horticulture farm in previous years (Meredith et al, 1989;Robertson et al, 1990Robertson et al, , 1991. The higher than normal rainfall and greater cloud cover in 1991 probably resulted in the Loring peaches being smaller and having lower total sugar contents than expected (Robertson et al, 1990).…”
Section: Discussionsupporting
confidence: 94%
“…Segundo Mitchell (1989), o maior teor de açúcar é encontrado nos pêssegos de maturação mais avançada. Ventura et al (1992) e Robertson et al (1993), trabalhando com pêssegos cv. Cresthaven, observaram variações no teor de SST durante o armazenamento, representadas por um leve aumento no início do período de armazenamento e posterior diminuição no conteú-do de SST, mantendo os valores iniciais.…”
Section: Resultsunclassified
“…Quando as frutas são armazenadas em baixas temperaturas, pouca evolução ocorre. No entanto, quando as frutas são expostas a temperaturas em torno de 20ºC, ocorre rápido incremento na coloração característica da fruta (Robertson et al, 1993).…”
Section: Resultsunclassified
“…Estos cambios se vieron reflejados con un aumento de los parámetros a * y b * en el CF. Resultados similares han sido descritos en otras variedades de fruta de hueso, con un aumento del parámetro a * (Delwiche y Baumgardner, 1985;Meredith et al, 1989;Robertson et al, 1990;1991; y b * (Delwiche y Baumgardner, 1985;Fernández-Trujillo y Artés, 1998).…”
Section: Fruta De Hueso: Melocotón Nectarina Y Albaricoqueunclassified